The construction of Uhuru party group identity in Zimbabwe: a textual analysis of revolutionary songs in Shona - Manyawu, Andrew T. (National Inquiry Services Centre, 2016)
Since Zimbabwe's 1970s liberation war, the Zimbabwe African National Union (Patriotic Front) (ZANU-PF) has used song to develop its group identity. During the war, choirs related to the party's military wing, the Zimbabwe African National Liberation Army, sang in support of the party's war effort. After independence, various groups have sung to promote ZANU-PF. This article examines texts of ZANU-PF songs from the liberation war and the Fast Track Land Reform Programme of the early 2000s, two landmarks in Zimbabwe's Liberation Struggle, Chimurenga. The Critical Discourse Analysis concept of identity frames this textual analysis. The article finds that through the songs examined here, ZANU-PF self-qualifies as the party of Chimurenga. The ZANU-PF concept of Chimurenga is heterogeneous as it draws upon various other ideologies, such as Maoism, and the dogma of ‘the children of the soil’. That heterogeneity is homogenized so as to enable the party to portray itself as perfect deliverer and guarantor of Black liberation, and rival political formations as traitors of Chimurenga.